О влиянии сферических лунок на поверхности лопаток диффузора на рабочий процесс ступени центробежного компрессора - Зинченко, Игорь Николаевич; Скорик, Андрей Викторович; Парафейник, Владимир Петрович (НТУ "ХПИ", 2016)
Представлены результаты численного исследования влияния сферических лунок, размещённых на поверхности лопаток диффузора, на интегральные характеристики ступени центробежного компрессора. Применение лунок рассматривается совместно с задачей увеличения запаса по помпажу. Увеличение запаса по помпажу обеспечивается за счёт модификации геометрии лопаточного диффузора базовой ступени (поворота лопаток), а лунки применяются для увеличения эффективности ступени в правой части газодинамической характеристики.

The purpose of the paper is to show how the spherical dimples located on vaned diffuser of centrifugal compressor effect on its performance. Centrifugal compressor stage with different modifications of vaned diffuser was calculated using ANSYS CFX. Vanes of the diffuser were turned to decrease the inlet angle of the vanes. This provides shifting of the stage characteristic in the direction of the low mass flow rate. Dimples were located on the vane surface of this modified diffuser with the aim of improving stage performance at the range of negative incidence angles at vane leading edge. The results of numerical computation showed that proposed location of the dimples provides the reducing of the flow separation zone and boundary layer thickness in the diffuser at negative incidence angles and, thus, increasing the efficiency of the compressor stage at corresponding mass flow range. The results of the investigation should be considered as qualitative. The accuracy of the simulation of the complex swirling flows with separation strongly depends on the CFX set-up. Therefore in order to obtain quantitative results a detailed verification (with experimental data) of the flow pattern and diffuser character-istics should be performed.
On the effect of spherical dimples at diffuser vane surface on performance of centrifugal compressor
Keywords: отрыв потока; интегральные характеристики; численное исследование; проточная часть; пограничный слой; flow separation; numerical simulation